2019
DOI: 10.1089/scd.2018.0170
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiac-Mesenchymal Stem Cell-Like Cells, a Novel Cell Population with Therapeutic Potential

Abstract: Cardiac stem/progenitors are being used in the clinic to treat patients with a range of cardiac pathologies. However, improvements in heart function following treatment have been reported to be variable, with some showing no response. This discrepancy in response remains unresolved. Mesenchymal stem cells (MSCs) have been highlighted as a regenerative tool as these cells display both immunomodulatory and proregenerative activities. The purpose of this study was to derive a cardiac MSC population to provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In our results, CMSCs expressed only GATA4, but not NKX2-5. Other studies using CS/CPCs from rotating tissue-culture conditions similar to our work, have also reported that GATA4 is expressed with limited expression of NKX2-5, which proposed these cells in early developmental stages (11,36). Therefore, our cells may also be considered to be in early developmental stages before expressing NKX2-5, and further analysis will help us understand the roles of CS/CPCs at various developmental stages or marking various kinds of stemness during primary culture.…”
Section: Cd105supporting
confidence: 78%
“…In our results, CMSCs expressed only GATA4, but not NKX2-5. Other studies using CS/CPCs from rotating tissue-culture conditions similar to our work, have also reported that GATA4 is expressed with limited expression of NKX2-5, which proposed these cells in early developmental stages (11,36). Therefore, our cells may also be considered to be in early developmental stages before expressing NKX2-5, and further analysis will help us understand the roles of CS/CPCs at various developmental stages or marking various kinds of stemness during primary culture.…”
Section: Cd105supporting
confidence: 78%
“…Furthermore, CD166 or activated leukocyte cell adhesion molecule (ALCAM), an important marker which is expressed in cardiac progenitors involved in heart development [21,22] and morphogenesis in xenopus [23] and mice [21], was found present in yCCs but absent in the proliferative clonogenic aCC population, a similar expression pattern was also previously reported in senescence CCs [24]. Hence, it is possible that CD90 Pos /CD140 Pos /CD166 Neg aCCs resemble a more mesenchymal-like stem cell phenotype and its emergence in CC population is a result of ageing, [25,26,27] albeit require confirmation from in vivo study.…”
Section: Discussionmentioning
confidence: 58%
“…This may in part explain the failure of pre-clinical trials to translate clinically into regenerative therapies [30]. Preclinical studies showing successful cell regenerative therapies use young healthy animals [57,58], whereas the prevalence of CVD increases linearly with age [59], and therefore, most patients undergoing cellular therapy are likely to display high levels of myocardial senescence [17,60] which could create an unfavourable environment impeding incorporation and differentiation of the transplanted cell populations [30,61]. Senolytic-mediated elimination of senescent cells from aged patients may, therefore, have the potential to improve the outcomes of such regenerative cellular therapies.…”
Section: Pharmaceutical Targeting Of Senescence To Improve Myocardialmentioning
confidence: 99%